Kepemimpinan Karismatik Dalam Membangun Mutu Performa Guru Pendidikan Diniyah Formal Ulya di Pondok Pesantren Nurul Jadid - Muhammad Fadali Amar; Muhib Ainul Yaqin (CV Edujavare Publishing, 2023)
Education is a necessity for everyone to improve the quality of human resources. As a means of supporting education, the pattern of leadership plays an important role in its implementation. In supporting quality cadres, good quality teacher performance is needed. In this regard, charismatic leadership is an effort to build the quality of teacher performance. All educational institutions certainly want the quality of the performance of existing teachers to continue to improve, one of those is the Ulya Formal Diniyah Education in Pesantren Nurul Jadid which is the object of this research. This research is a field research using a qualitative approach. Data collection is done by observation, interviews and documentation. Based on the results of the research that has been done, it can be concluded that as an effort to build teacher performance quality, a clear and targeted vision and mission is implemented, quality learning sistems and strategies, intense training and evaluation of teacher performance and maximum charismatic leadership patterns. It was also found that the head of Ulya Diniyah Formal Education is a charismatic leader with democratic characteristics, puts forward one vision, confident, sensitive to the environment and an agent of change. Thus, this has a significant impact on the quality of teacher performance which is expected to continue to improve and develop by complying with and respecting the policies brought by the leader.